2019 Alzheimer's disease facts and figures (Alzheimer's & dementia, 2019)
This article describes the public health impact of Alzheimer's disease (AD), including incidence and prevalence, mortality and morbidity, use and costs of care, and the overall impact on caregivers and society. The Special Report examines the use of brief cognitive assessments by primary care physicians as a tool for improving early detection of dementia. An estimated 5.8 million Americans have Alzheimer's dementia. By mid-century, the number of people living with Alzheimer's dementia in the United States may grow to 13.8 million, fueled in large part by the aging baby boom generation. In 2017, official death certificates recorded 121,404 deaths from AD, making AD the sixth leading cause of death in the United States and the fifth leading cause of death among Americans age ≥65 years. Between 2000 and 2017, deaths resulting from stroke, heart disease, and prostate cancer decreased, whereas reported deaths from AD increased 145%. In 2018, more than 16 million family members and other unpaid caregivers provided an estimated 18.5 billion hours of care to people with Alzheimer's or other dementias. This care is valued at nearly $234 billion, but its costs extend to family caregivers' increased risk for emotional distress and negative mental and physical health outcomes. Average per-person Medicare payments for services to beneficiaries age ≥65 years with Alzheimer's or other dementias are more than three times as great as payments for beneficiaries without these conditions. Total payments in 2019 for health care, long-term care and hospice services for people age ≥65 years with dementia are estimated to be $290 billion. Early detection of Alzheimer's offers numerous medical, emotional and financial benefits—benefits that accrue to affected individuals and their families as well as to society at large. Alzheimer's Association surveys regarding brief cognitive assessments for detection of dementia found that while a large majority of seniors and primary care physicians say the assessments are important, only half of seniors have received an assessment, and only 16 percent of seniors receive regular cognitive assessments. Many educational opportunities exist to facilitate increased use of brief cognitive assessments in the primary care setting.